Getting Classics into Secondary Schools: Three Case Studies - Steven Hunt (The Journal of Classics Teaching, 2018)
Despite the challenges which are involved, some secondary schools show determination to get Classics onto the timetable and into their curricular provision. The following three case studies draw on interviews with the people directly involved in doing so: the Principals and the teachers themselves. These experiences were captured at the time when they were getting Classics into their schools. The first is derived from an interview with a qualified specialist Classics teacher, ‘Rachel’, working in London. Latin already had a presence there from when the school had employed a part-time teacher; the remit was the development of a full Classics department. The second is based on interviews with the school head teacher and a non-specialist Modern Languages teacher ‘Yvonne’ who had been employed to start a Classics department from scratch in a school in the Midlands. The third is based on an interview with the Principal of an academy which had decided to introduce Latin not only into her own school with a new teacher ‘George’, but also into one that was not yet built. The respondents’ real names have, of course, been changed.